Perkembangan Agama dan Moral Peserta Didik dalam Perspektif Barat dan Timur: Studi Pemikiran Lawrence Kohlberg dan Ibnu Miskawaih - Tomi Adana Hasyim; Nabila Bilqisti; Rismayana Johan; Kemalawati (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2026)
The religious and moral development of students is an important element in education because it is closely related to the formation of character, attitudes, and individual social behavior. The rapid dynamics of modern life have brought various influences on the mindset and behavior of younger generations, making the strengthening of moral and religious education an unavoidable necessity. This study aims to analyze the religious and moral development of students through two perspectives, namely the Western perspective represented by Lawrence Kohlberg and the Eastern Islamic perspective represented by Ibn Miskawaih. This research employs a library research method with a qualitative descriptive approach based on various relevant scientific literatures. The findings indicate that Lawrence Kohlberg views moral development as a gradual process influenced by individuals’ reasoning abilities and cognitive development in making ethical decisions. On the other hand, Ibn Miskawaih emphasizes that morality is closely related to character building, self-control, and continuous spiritual development. Both thinkers have made significant contributions to moral education; however, Ibn Miskawaih’s concept is considered more comprehensive because it integrates moral aspects with religious values and personality formation. Therefore, students’ moral education should not merely focus on rational development, but also on spiritual guidance and exemplary conduct in daily life.